2018
DOI: 10.3928/01484834-20180522-08
|View full text |Cite
|
Sign up to set email alerts
|

Writing Across the Curriculum: Reliability Testing of a Standardized Rubric

Abstract: Investigators recommend effective faculty orientation for rubric use and future work in developing a rubric to assess reflective writing. [J Nurs Educ. 2018;57(6):366-370.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Two studies examined standardizing writing rubrics to be used in a WAC program. Minnich et al (2018) reported high interrater reliability among faculty using the scholarly writing rubric. Abbott and Shaw (2019) shared their success in creating a hybrid standardized rubric for writing that had common areas of assessment and individualized areas depending on the course's focus.…”
Section: Providing Clear Writing Expectationsmentioning
confidence: 99%
“…Two studies examined standardizing writing rubrics to be used in a WAC program. Minnich et al (2018) reported high interrater reliability among faculty using the scholarly writing rubric. Abbott and Shaw (2019) shared their success in creating a hybrid standardized rubric for writing that had common areas of assessment and individualized areas depending on the course's focus.…”
Section: Providing Clear Writing Expectationsmentioning
confidence: 99%
“…They demonstrated that using a rubric scoring scale is appropriate for assessing the practical competence of students since it may translate qualitative criteria into quantitative forms on a grading scale. Most rubric development and implementation research focus on subjective assessments only (Grainger, 2021;Minnich et al, 2018;Schuller et al, 2019;Stanley et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…14,15,[23][24][25] Although some resulted in decreased grade inflation, 14 high internal consistency ratings, 24 and interrater reliability, 23 the instruments were not readily applicable to DNP students due to the course-specific nature of the rubric, 14,24 criteria that were too broad to distinguish specific skills, 14,25 or the lack of advanced scientific writing skills, such as synthesis and critical appraisal. 23 Roush and Tesoro 26 developed the Doctor of Nursing Practice Project Critical Appraisal Tool (DNP-PCAT) to assess DNP Project quality and rigor. It is a 141-point, 16component instrument with 14 focused on content and 2 pertaining to writing.…”
Section: Rubricsmentioning
confidence: 99%
“…Some focused on scientific writing skills particular to the content and conventions of health science writing. They measured reference use, paraphrasing, direct quotes, and plagiarism 14,15,23-25 . Although some resulted in decreased grade inflation, 14 high internal consistency ratings, 24 and interrater reliability, 23 the instruments were not readily applicable to DNP students due to the course-specific nature of the rubric, 14,24 criteria that were too broad to distinguish specific skills, 14,25 or the lack of advanced scientific writing skills, such as synthesis and critical appraisal 23 …”
Section: Rubricsmentioning
confidence: 99%